Implementasi Sistem Layanan Cuci Kendaraan Panggilan Berbasis Website pada Jasa Carenmore - Dina Dwi Arika; Dinda Amalia Julyandri; Fatkhur Rozak; Lukman Lukman; Sholihah Ayu Wulandari (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
The rapid development of information technology has provided great opportunities for the service sector to improve efficiency and convenience, including in vehicle washing services. This research aims to develop a web-based system using the Laravel framework, which is designed to simplify the online ordering process and overcome queuing problems. The system features user authentication, location-based booking, payment gateway integration for real-time transactions, and an interactive dashboard for service providers. The case study was conducted at Carenmore, a vehicle wash service in Krian. The implementation results show that the system is able to reduce customer waiting time, provide a better user experience, and improve service efficiency. Further development is recommended to add a variety of features, improve interface design, and increase the system's ability to handle larger user loads.